(untitled) (Journal of the College of Basic Education, 2022)
In our research tagged (The Resurrection in the Holy Qur’an - Interpretation of Al-Amthal as a Model - Objective Study), we explained the following:The life of the Grand Ayatollah, Sheikh Nasser Makarem Al-Shirazi, as it dealt with his name and lineage, his birth and upbringing, his most prominent students, and his scientific effects.Then we stopped after that to explain the concept of the resurrection and the suspicion of eating and what is eaten, as it dealt with the resurrection in the language, and in the terminology of the speakers, and to explain the sayings of the scholars in that, as well as the statement of the suspicion of eating and what is eaten.The name of the Resurrection was mentioned in the Holy Qur’an in many verses of the Noble Qur’an, and with different and varied expressions and expressions, and each of them indicates the resurrection of the Hour and the re-creation after their death again, and these verses are considered conclusive evidence and proofs of the Resurrection and recompense, reckoning and punishment, reward and return to God Almighty exalted be He,